Patterns of Aedes aegypti abundance, survival, human-blood feeding and relationship with dengue risk, Kenya - Kamau, Winnie W.; Sang, Rosemary; Rotich, Gilbert; Agha, Sheila B.; Menza, Nelson; Torto, Baldwyn; Tchouassi, David P. (Frontiers in Tropical Diseases, 2023)
Dengue virus (DENV) transmission risk is influenced by the bionomic traits of the key vector, Aedes aegypti. We investigated patterns of abundance, survival, and human blood-feeding of Ae. aegypti populations in two environments in Kenya: peri-urban Rabai (coastal Region, dengue-endemic) and rural Kerio Valley (Rift Valley Region, no reported dengue outbreak). In both environments, Ae. aegypti survival (estimated by parity), was inversely correlated with vector abundance, and this was influenced by weather conditions, notably temperature and relative humidity. In Rabai, Ae. aegypti mostly fed on humans (human blood index=51%), a pattern that corroborates with dengue cases in the coastal region. Aedes aegypti additionally, exhibited opportunistic feeding (livestock, rodents, reptiles, birds), suggesting the risk of human exposure to zoonotic pathogens via spillover transmission events aided by the vector. Abundance and human blood-feeding rates were consistently lower in Kerio Valley likely related to the degree of urbanization. Remarkably, the periods of high human feeding in Rabai coincided with high vector survival rates, a trend that could potentially drive intense DENV transmission at certain times of the year. We found a genetic influence of Ae. aegypti on the degree of anthropophagy but this could be influenced by potential seasonal shifts in human feeding. The findings of this study have implications both for DENV transmission risk and vector control strategies, but also in modeling which should integrate vector bionomic factors beyond vector abundance.